(untitled) (American Journal of Islam and Society, 2007)
AwqafSA (www.awqafSA.org.za), a South African Muslim NGO, has been in constant contact with IRCICA (the Islamic Research Centre for Islamic History, Art and Culture: www3.ircica.org), an affiliate of the Organization of the Islamic Conference, for several years regarding possible cooperation. On 18 April 2005, this contact culminated in Halit Eren’s (director-general, IRCICA) meeting with a few organizations and their representatives regarding the forthcoming “International Symposium on Islamic Civilization in Southern Africa,” scheduled for the following year. AwqafSA and IRCICA, aware of the fact that very little research has been done on Islam in southern Africa, have strongly advocated holding a symposium to bring scholars, researchers, and stakeholders together to share their thoughts on their respective countries and communities. At this meeting, it was agreed that AwqafSA would be the local host in partnership with IRCICA and that the University of Johannesburg would be the third partner in this important historical venture. The symposium took place between 1-3 September 2006 at the University of Johannesburg. A few months earlier, on 28 June 2006 to be exact, Ebrahim Rasool (premier, Western Cape Province) formally launched the symposium at Leeuwenhof, his official residence. In his short speech, he stressed the multicultural nature of South African society and the importance of holding such a symposium in the country, a symposium that will allow participants – particularly South Africans – to do some “rainbow gazing” and critically assess their position within South Africa. The premier was also one of the keynote speakers at the symposium. Essop Pahad (minister, Office of the President) connected the symposium proceedings to the African Renaissance process as well as to the significant Timbuktu Project (www.timbuktufoundation.org; www.timbuktuheritage.org) spearheaded by Shamil Jeppie (the University of Cape Town). He also touched upon new evidence of the influence of Islam in the Limpopo Valley, northern South Africa. In his concluding remarks, he emphatically rejected Huntington’s “clash of civilizations” thesis ...